Games of the X Olympiad in Los Angeles 1932: The Story of the Czechoslovak Olympic Team - Zdeněk Škoda (Jan Długosz University in Częstochowa, 2019)
A lot has been already written on the Czechoslovak results at the Games of the X Olympiad in Los Angeles in 1932. However, not much is known about the journey of the Czechoslovak team to the venue and back. This text focuses on this adventure, describing the problems that the Czecho-slovakian team faced in the context of the economic crisis, the actual journey to the United States on board the steamship, the trip across the United States, the encounters with Czechoslovak com-patriots and American politicians, sporting successes at the Olympic Games and the spectacular return of Czechoslovak athletes to Prague. The method used for this paper is the historical method. Primary sources were the main sources of information, mainly the estate of the General Secretary of the Czechoslovak Olympic Committee, František Widimský, his memoirs, period articles and unique photographs from the archive of the Czech Olympic Committee. Thanks to these sources, the entire course of the journey was successfully reconstructed.